2020
DOI: 10.1155/2020/5196302
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Pharmacology Approach for Identifying the Multiple Mechanisms of Action for the Rougui‐Fuzi Herb Pair in the Treatment of Cardiocerebral Vascular Diseases

Abstract: Cardiocerebral vascular diseases (CCVDs) are the main reasons for high morbidity and mortality all over the world, including atherosclerosis, hypertension, myocardial infarction, stroke, and so on. Chinese herbs pair of the Cinnamomum cassia Presl (Chinese name, rougui) and the Aconitum carmichaelii Debx (Chinese name, fuzi) can be effective in CCVDs, which is recorded in the ancient classic book Shennong Bencao Jing, Mingyibielu and Thousand Golden Prescriptions. However, the active ingredients and the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The lower the binding energy, the more stable the binding conformation of the receptor and the ligand. The binding energy −5.0 kcal/mol is set as the threshold to determine whether the binding of the receptors and ligands is good or not ( Li et al, 2020 ). Therefore, we screened out the ligand which binds the best (with the lowest energy) to the receptor based on the binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…The lower the binding energy, the more stable the binding conformation of the receptor and the ligand. The binding energy −5.0 kcal/mol is set as the threshold to determine whether the binding of the receptors and ligands is good or not ( Li et al, 2020 ). Therefore, we screened out the ligand which binds the best (with the lowest energy) to the receptor based on the binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…Fuzi, the processed lateral root of Aconitum carmichaelii Debeaux (Ranunculaceae), is an herb extensively used in TCM to treat the diseases with cold symptoms because of its hot property, which was originally recorded in Shennong Bencao Jing ( Zheng et al, 2014 ; Li C. et al, 2020 ) . In Bencao Jingdu , it was viewed as the key TCM to ameliorate Yang deficiency and rescue the patient from prostration ( Zhou et al, 2015 ).…”
Section: The Important Hot and Cold Traditional Chinese Medicines Andmentioning
confidence: 99%
“…For example, both Fuzi and Rougui are hot TCMs; however, they cannot be used interchangeably in the clinic in most cases. A previous study based on network pharmacology to explore the mechanism of Fuzi and Rougui in the treatment of cardiocerebral vascular diseases showed that, among the 194 targets of Fuzi and Rougui, 45 targets are shared; that is, three-quarters of the targets are different ( Li C. et al, 2020 ). In addition, from a metabolic perspective, Fuzi can promote energy metabolism by increasing the activity of Na + -K + -ATPase and Ca 2+ -Mg 2+ -ATPase enzymes in hepatocytes, which is closely related to thermogenesis ( Yu et al, 2012 ).…”
Section: Perspectivesmentioning
confidence: 99%
“…Network pharmacology explains the therapeutic effect of herb pairs. 104 We cross-referenced the chemical compositions of C. yanhusuo with the pharmacological functions mentioned in the Chinese Medicine System Pharmacology Database. Using the systems pharmacology analysis platform TCMSP (http:// bigd.…”
Section: Network Pharmacologymentioning
confidence: 99%